The SPES3 Experimental Facility Design for the IRIS Reactor Simulation - Mario Carelli; Lawrence Conway; Milorad Dzodzo; Andrea Maioli; Luca Oriani; Gary Storrick; Bojan Petrovic; Andrea Achilli; Gustavo Cattadori; Cinzia Congiu; Roberta Ferri; Marco Ricotti; et al. (Science and Technology of Nuclear Installations)
IRIS is an advanced integral pressurized water reactor, developed by an international consortium led by Westinghouse. The licensing process requires the execution of integral and separate effect tests on a properly scaled reactor simulator for reactor concept, safety system verification, and code assessment. Within the framework of an Italian R&D program on Nuclear Fission, managed by ENEA and supported by the Ministry of Economic Development, the SPES3 facility is under design and will be built and operated at SIET laboratories. SPES3 simulates the primary, secondary, and containment systems of IRIS with 1 : 100 volume scale, full elevation, and prototypical thermal-hydraulic conditions. The simulation of the facility with the RELAP5 code and the execution of the tests will provide a reliable tool for data extrapolation and safety analyses of the final IRIS design. This paper summarises the main design steps of the SPES3 integral test facility, underlying choices and phases that lead to the final design.